Do Remittances Enhance Financial Inclusion in LMICs and in Fragile States? - Ben Naceur, Sami (IMF Working Papers; Working Paper, 2020)
This paper explores the relationship between remittances and financial inclusion for a sample of 187 countries over the period 2004-2015, using cross-country as well as dynamic panel GMM regressions. At low levels of remittances-to-GDP, these flows act as a substitute to formal financial channels, thereby reducing financial inclusion. In contrast, when remittance-to-GDP ratio is high, above 13% on average, they tend to complement formal access and usage channels, thus enhancing financial inclusion. This 'U shaped' relationship highlights the role of remittance flows in financing household consumption at low levels, while raising formal household bank savings and allowing for more intermediation, at high levels of remittance-to-GDP.